Pengembangan Media Pembelajaran Pengenalan Perangkat Keras Jaringang Komputer Berbasis Augmented Reality - Setiawan, Muhamad Anjas; Widodo, Tri (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
In Indonesia, many educators still apply conventional methods, namely by reading questions to students which are then answered using paper media, which are often considered less effective in attracting students' interest in learning. One of them is in the material on the introduction of computer network hardware. The purpose of this study is to create Augmented reality (AR)-based learning media for the introduction of computer network hardware in order to create a fun and non-boring learning process for students. The process of creating learning media is carried out by applying the Multimedia Development Life Cycle (MDLC) method. This study resulted in an application of computer network hardware learning media based on augmented reality. This application is equipped with learning materials, learning objectives, images and 3D objects. Based on the validation results, the application obtained a feasibility level of 86.12% from media experts, 84.45% from material experts, and 79.37% from user tests (students). These findings indicate that the application of AR not only increases visual appeal, but also supports conceptual understanding through immersive visual representations. The main contribution of this study lies in the systematic application of the MDLC framework in the development of AR learning media, as well as the integration of 3D objects designed according to pedagogical needs in the context of ICT education.